Negative electrode for non-aqueous electrolyte secondary battery and non-aqueous electrolyte secondary battery including the same
By employing a porous metal body current collector and strategically arranging negative electrode materials with a silicate-based skeletal forming agent, the energy density and durability of nonaqueous electrolyte secondary batteries are enhanced, addressing manufacturing and performance limitations in conventional designs.
Patent Information
- Application Number
- JP2021014417
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-01
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2041-02-01
AI Technical Summary
Conventional nonaqueous electrolyte secondary batteries face limitations in energy density due to constraints on the thickness and active material loading of the negative electrode, leading to issues like coating unevenness, cracks, and peeling during manufacturing.
The use of a porous metal body as a current collector, combined with a specific arrangement of negative electrode materials and a skeletal forming agent containing silicate with siloxane bonds, enhances the permeability of the skeletal forming agent and improves the structural integrity and durability of the negative electrode.
This configuration effectively suppresses structural deterioration and enhances cycle durability, allowing for increased energy density and improved performance of nonaqueous electrolyte secondary batteries.
Smart Images

Figure 0007657061000002 
Figure 0007657061000003 
Figure 0007657061000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode for a non-aqueous electrolyte secondary battery and a non-aqueous electrolyte secondary battery including the same. [Background technology]
[0002] In recent years, non-aqueous electrolyte secondary batteries such as lithium ion secondary batteries are increasingly being used in automobiles and the like because they are small, lightweight, and provide high output. A non-aqueous electrolyte secondary battery is a general term for a battery system that uses an electrolyte that does not contain water as a main component, and is a chargeable and dischargeable power storage device. For example, lithium ion batteries, lithium polymer batteries, lithium solid-state batteries, lithium air batteries, lithium sulfur batteries, sodium ion batteries, potassium ion batteries, multivalent ion batteries, fluoride batteries, sodium sulfur batteries, and the like are known. This non-aqueous electrolyte secondary battery is mainly composed of a positive electrode, a negative electrode, and an electrolyte. In addition, when the electrolyte has fluidity, a separator is further interposed between the positive electrode and the negative electrode.
[0003] For example, a technique has been disclosed in which a skeletal former containing a silicate having a siloxane bond is present at least on the surface of an active material, and the skeletal former is allowed to penetrate from the surface to the inside, in order to improve the battery life (see, for example, Patent Document 1). This technique is said to be able to form a strong skeleton in the active material, thereby improving the battery life. Also disclosed is a technique in which the skeletal former is applied to a negative electrode containing a silicon (Si)-based active material (see, for example, Patent Document 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 6369818 [Patent Document 2] Patent No. 6149147 Summary of the Invention [Problem to be solved by the invention]
[0005] Meanwhile, there is a demand for improving the energy density of the non-aqueous electrolyte secondary battery. In order to improve the energy density, it is considered effective to increase the thickness of the negative electrode and to increase the density of the amount of negative electrode active material. However, in the conventional technology, there is a limit to the thickness of the negative electrode in terms of the production of the negative electrode. Specifically, the practical thickness of the film that can be applied to the conventional current collector foil for the mixture layer is less than 100 μm. If the film thickness is 100 μm or more, problems such as uneven coating, cracks, and peeling occur, making it difficult to produce a highly accurate negative electrode.
[0006] In addition, due to the balance between the binding strength of the binder and the expansion and contraction of the negative electrode active material, there is a limit to the amount of negative electrode active material per unit area from the viewpoint of durability. Specifically, the negative electrode active material capacity per unit area is 4 mAh / cm 2 On the other hand, the active material capacity is limited to about 4 mAh / cm2 (film thickness 50 μm), and sufficient cycle performance cannot be maintained at a thickness greater than this. 2 If the thickness is less than this, no improvement in energy density can be expected.
[0007] In order to solve the above problems, it is considered to apply a porous metal body to the negative electrode current collector of a non-aqueous electrolyte secondary battery and fill the porous metal body with an electrode mixture. In a non-aqueous electrolyte secondary battery, when a current collector made of a porous metal body, an electrode active material made of a silicon-based material as a negative electrode active material, and a framework forming agent that coats the current collector and the electrode active material are applied to the negative electrode, it has been found that the penetration of the inorganic binder into the inside of the current collector pores is insufficient. It has also been found that a non-aqueous electrolyte secondary battery using such a negative electrode causes structural deterioration inside the electrode due to repeated charging and discharging, which deteriorates the battery performance.
[0008] Therefore, there is a need for a negative electrode for a nonaqueous electrolyte secondary battery that can suppress structural deterioration of the electrode and improve cycle durability by improving the permeability of a framework-forming agent into a current collector made of a porous metal body, and a nonaqueous electrolyte secondary battery including the same.
[0009] The present invention has been made in view of the above, and has an object to provide a negative electrode for a nonaqueous electrolyte secondary battery that can suppress structural deterioration of the electrode and improve cycle durability by improving the permeability of a framework-forming agent into a current collector made of a porous metal body, and a nonaqueous electrolyte secondary battery including the same. [Means for solving the problem]
[0010] (1) In order to achieve the above object, the present invention provides a negative electrode for a non-aqueous electrolyte secondary battery, comprising: a current collector formed of a porous metal body; a first negative electrode material disposed in the pores of the porous metal body, the first negative electrode material having a negative electrode active material formed of a silicon-based material, a conductive assistant, and a binder; and a second negative electrode material disposed in the pores of the porous metal body, the second negative electrode material having a framework forming agent including a silicate having a siloxane bond, the first negative electrode material and the second negative electrode material being disposed in a pair of first regions formed on both outer sides in a thickness direction of the current collector, the first negative electrode material and the second negative electrode material being disposed in a second region formed in the center of the thickness direction of the current collector, the first negative electrode material being not disposed in the first negative electrode material and the second negative electrode material being disposed in the second negative electrode material.
[0011] (2) In order to achieve the above object, the present invention also provides a negative electrode for a non-aqueous electrolyte secondary battery, comprising: a current collector formed of a porous metal body; a first negative electrode material disposed in the pores of the porous metal body and having a conductive assistant; a second negative electrode material disposed in the pores of the porous metal body and having a negative electrode active material constituted by a silicon-based material and a binder; and a third negative electrode material disposed in the pores of the porous metal body and having a framework forming agent including a silicate having a siloxane bond, the first negative electrode material being disposed in a thickness direction of the current collector; and a second negative electrode material being disposed in a thickness direction of the current collector. The first negative electrode material is disposed in a thickness direction of the current collector. The second negative electrode material is disposed in a thickness direction of the current collector. The third negative electrode material is disposed in a thickness direction of the current collector. The second negative electrode material is disposed in a thickness direction of the current collector. The first negative electrode material is disposed in a thickness direction of the current collector.
[0012] (3) In the negative electrode for a non-aqueous electrolyte secondary battery according to (1) or (2), the framework-forming agent may contain a silicate represented by the following general formula (1): [C1] A2O·nSiO2···Formula (1) [In the above general formula (1), A represents an alkali metal.]
[0013] (4) In the negative electrode for a nonaqueous electrolyte secondary battery according to any one of (1) to (3), the second region may have a thickness of 0.5 to 15% of the total thickness of the negative electrode.
[0014] (5) In the negative electrode for a nonaqueous electrolyte secondary battery according to any one of (1) to (4), the porous metal body may be a foamed metal body.
[0015] (6) The present invention also provides a nonaqueous electrolyte secondary battery comprising a negative electrode for a nonaqueous electrolyte secondary battery according to any one of (1) to (5). Effect of the Invention
[0016] According to the present invention, it is possible to provide a negative electrode for a nonaqueous electrolyte secondary battery, which can suppress deterioration in durability and improve energy density by improving the permeability of a framework-forming agent into a current collector made of a porous metal body, and a nonaqueous electrolyte secondary battery including the same. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1 is a diagram illustrating a schematic configuration of the inside of a negative electrode for a nonaqueous electrolyte secondary battery according to a first embodiment of the present invention. [Diagram 2] FIG. 2 is a diagram illustrating a schematic configuration of a negative electrode for a nonaqueous electrolyte secondary battery according to a second embodiment of the present invention. [Diagram 3] FIG. 2 is a schematic diagram showing a state in which a negative electrode material is filled into a current collector made of a porous metal body to produce a negative electrode layer precursor in the first embodiment of the present invention. [Figure 4] FIG. 2 is a diagram illustrating a process for producing a negative electrode for a non-aqueous electrolyte secondary battery by impregnating the negative electrode layer precursor of FIG. 1 with a framework-forming agent in the first embodiment of the present invention. [Diagram 5]FIG. 11 is a schematic diagram showing a process for producing a negative electrode layer precursor by filling a current collector made of a porous metal body with a second conductive assistant and then filling the current collector with a negative electrode material in a second embodiment of the present invention. [Figure 6] FIG. 3 is a diagram illustrating a process for producing a negative electrode for a non-aqueous electrolyte secondary battery by impregnating the negative electrode layer precursor of FIG. 2 with a framework-forming agent in a second embodiment of the present invention. [Figure 7] FIG. 2 is a graph showing the relationship between the number of cycles and the discharge capacity in Examples 1 and 2 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] First Embodiment Hereinafter, a first embodiment of the present invention will be described in detail with reference to the drawings.
[0019] [Negative electrode] 1 is a diagram showing a schematic diagram of the internal structure of the negative electrode for a non-aqueous electrolyte secondary battery of the present invention. The negative electrode for a non-aqueous electrolyte secondary battery 1 according to this embodiment includes a current collector 11 made of a porous metal body, a first negative electrode material 12 arranged in the pores of the porous metal body and having a negative electrode active material 13 made of a silicon-based material, a conductive assistant 15, and a binder 16, and a second negative electrode material 19 arranged in the pores of the porous metal body and having a framework forming agent 14 including a silicate having a siloxane bond. The negative electrode 1 for a nonaqueous electrolyte secondary battery according to this embodiment has a pair of first regions 17 formed on a current collector 11 on both outer sides in the thickness direction of the current collector 11, in which a first negative electrode material 12 and a second negative electrode material 19 are arranged, and a second region 18 formed in the center in the thickness direction of the current collector, in which the first negative electrode material 12 is not arranged and the second negative electrode material 19 is arranged. For example, by applying this embodiment to a negative electrode for a lithium ion secondary battery, it is possible to provide a negative electrode for a lithium ion secondary battery that can suppress durability deterioration and structural deterioration of the electrode by improving the permeability of the framework forming agent into the inside of a current collector made of a porous metal body, and that can improve the energy density and cycle durability, and a lithium ion secondary battery including the same. Below, an example in which this embodiment is applied to a negative electrode for a lithium ion secondary battery will be described in detail, but various additions, modifications, and deletions are possible within the scope of the present invention.
[0020] A current collector made of a porous metal body is used as the current collector 11. Examples of the current collector include mesh, woven fabric, nonwoven fabric, embossed body, punched body, expanded body, and foamed body, and a metal foam body is preferably used. Among them, a metal foam body having a three-dimensional mesh structure with continuous pores is preferably used, and for example, Celmet (registered trademark) (manufactured by Sumitomo Electric Industries, Ltd.) can be used.
[0021] The material of the porous metal body is not particularly limited as long as it has electronic conductivity and can pass electricity through the held electrode material. For example, conductive metals such as Al, Al alloys, Ni, Ni-Cr alloys, Fe, Cu, Ti, Cr, Au, Mo, W, Ta, Pt, Ru, and Rh, and conductive alloys containing two or more of these conductive metals (stainless steels (SUS304, SUS316, SUS316L, YUS270, etc.) can be used. When a conductive metal or conductive alloy other than the above is used, it may have a multilayer structure of different metals, for example, Fe coated with Cu or Ni. Among them, Ni or a Ni alloy is preferably used because of its excellent electronic conductivity and reduction resistance.
[0022] The thickness of the porous metal body is preferably 10 μm or more, more preferably 50 μm or more, and is preferably 1 mm or less, more preferably 800 μm or less.
[0023] The average pore diameter of the porous metal body before pressing is preferably 100 μm to 850 μm. When the average pore diameter of the porous metal body is within this range, the distance between the negative electrode active material 13 filled or supported inside the porous metal body and the metal skeleton is stable, the electronic conductivity is improved, and an increase in the internal resistance of the battery is suppressed. In addition, even if a volume change occurs due to charging and discharging, the electrode mixture can be prevented from falling off.
[0024] The specific surface area of the porous metal body is preferably 1000 to 10000 m 2 / m 3 This is 2 to 10 times the specific surface area of a conventional current collector foil. When the specific surface area of the porous metal body is within this range, the contact between the electrode mixture and the current collector 11 is improved, and an increase in the internal resistance of the battery is suppressed. A more preferable specific surface area is 4000 to 7000 m. 2 / m 3 It is.
[0025] The porosity of the porous metal body is preferably 90 to 99%. When the porosity of the porous metal body is within this range, it is possible to increase the amount of electrode mixture to be filled, and the energy density of the battery is improved. Specifically, when the porosity exceeds 99%, the mechanical strength of the porous metal body is significantly reduced, and the porous metal body is easily damaged by the volume change of the electrode accompanying charging and discharging. Conversely, when the porosity is less than 90%, not only the amount of electrode mixture to be filled is reduced, but also the ionic conductivity of the electrode is reduced, making it difficult to obtain sufficient input / output characteristics. From these viewpoints, a more preferable porosity is 93 to 98%.
[0026] The electrode weight of the porous metal body is preferably 1 to 100 mg / cm 2 When the electrode area density of the porous metal body is within this range, the active material capacity can be fully expressed, and the electrode can exhibit the capacity as designed. A more preferable electrode area density is 5 to 60 mg / cm. 2 It is.
[0027] The negative electrode active material 13 is one capable of reversibly absorbing and releasing lithium ions, and specifically, a negative electrode active material composed of a high-capacity silicon-based material is used. Examples of silicon-based materials include silicon alone, silicon alloys, silicon oxides, silicon compounds, and the like. Here, silicon alone refers to crystalline or amorphous silicon with a purity of 95% by mass or more. The silicon alloy refers to a Si-M alloy consisting of silicon and another transition element M, where M is, for example, Al, Mg, La, Ag, Sn, Ti, Y, Cr, Ni, Zr, V, Nb, Mo, and the like, and may be a complete solid solution type alloy, a eutectic alloy, a hypoeutectic alloy, a hypereutectic alloy, or a peritectic type alloy. The silicon oxide refers to an oxide of silicon or a complex consisting of silicon alone and SiO2, and the element ratio of Si to O may be 1:1.7 or less. The silicon compound is a substance in which silicon and two or more other elements are chemically bonded. Among these, silicon alone is preferable because it can form an interface layer described later well. Alternatively, a mixture or composite of a silicon-based material and a carbon-based material may be used.
[0028] The shape of the silicon-based material is not particularly limited, and may be a spherical, elliptical, faceted, strip-like, fibrous, flake-like, doughnut-like, or hollow powder, and these may be single particles or granules.
[0029] The negative electrode active material 13 made of a silicon-based material has an expansion rate of 10% or more due to charging and discharging. That is, the negative electrode active material 13 expands and contracts significantly during charging and discharging, but by using the framework forming agent 14 described later, it is possible to suppress deterioration in durability due to such expansion and contraction.
[0030] From the viewpoint of obtaining excellent cycle characteristics of the electrode and high input / output characteristics, the particle size of the silicon-based material is preferably 1.0 μm to 15 μm.
[0031] In this embodiment, the second negative electrode material 19 includes a framework forming agent 14 . A skeleton-forming agent 14 containing a silicate having a siloxane bond is used as the skeleton-forming agent 14. More specifically, the skeleton-forming agent 14 preferably contains a silicate represented by the following general formula (1). [Case 2] A2O·nSiO2···Formula (1)
[0032] In the above general formula (1), A represents an alkali metal. Among them, A is preferably at least one of lithium (Li), sodium (Na) and potassium (K). By using such an alkali metal salt of silicic acid having a siloxane bond as a framework forming agent, a lithium ion secondary battery having high strength, excellent heat resistance and excellent cycle life can be obtained.
[0033] In the above general formula (1), n is preferably 1.6 or more and 3.9 or less. When n is within this range, an appropriate viscosity is obtained when the skeletal forming agent 14 is mixed with water to form a skeletal forming agent liquid, and as described below, when the skeletal forming agent 14 is applied to a negative electrode containing silicon as the negative electrode active material 13, the skeletal forming agent 14 is easily permeated into the negative electrode material 12. Therefore, a lithium ion secondary battery with high strength, excellent heat resistance, and excellent cycle life can be more reliably obtained. More preferably, n is 2.0 or more and 3.5 or less.
[0034] The silicate is preferably amorphous. Since an amorphous silicate has a disordered molecular arrangement, it does not break in a specific direction like a crystal. Therefore, by using an amorphous silicate as the framework forming agent 14, the cycle life characteristics are improved.
[0035] For example, by applying the above-mentioned skeletal former liquid to a negative electrode containing silicon as the negative electrode active material 13, the skeletal former 14 penetrates between the negative electrode active material 13. Then, it is presumed that the silicon constituting the negative electrode active material 13 and the above-mentioned silicate constituting the skeletal former 14 fuse together, and that, for example, the hydrolyzed silicate undergoes a dehydration reaction (condensation reaction of silanol groups) by heating to form a siloxane bond (-Si-O-Si-). That is, in the negative electrode 1 for a lithium ion secondary battery of this embodiment, an interface layer made of an inorganic substance is formed at the interface between the negative electrode active material 13 and the skeletal former 14, and this interface layer contains silicon derived from the siloxane bond and an alkali metal generated by hydrolysis of the silicate or the like. It is presumed that the presence of this interface layer firmly bonds the negative electrode active material 13 and the skeletal former 14, resulting in excellent cycle life characteristics.
[0036] In this embodiment, the ratio of alkali metal atoms to all constituent atoms of the interface layer is preferably higher than the ratio of alkali metal atoms to all constituent atoms of the skeleton forming agent 14. More specifically, the ratio of alkali metal atoms to all constituent atoms of the interface layer is preferably 5 times or more the ratio of alkali metal atoms to all constituent atoms of the skeleton forming agent 14. This makes the bond between the negative electrode active material 13 and the skeleton forming agent 14 stronger, and peeling due to expansion and contraction of the negative electrode active material 13 during charging and discharging and the occurrence of wrinkles and cracks in the current collector 11 are further suppressed, thereby improving the cycle life.
[0037] The thickness of the interface layer is preferably 3 to 30 nm. When the thickness of the interface layer is within this range, the bond between the negative electrode active material 13 and the framework forming agent 14 becomes stronger, peeling due to expansion and contraction of the negative electrode active material 13 during charging and discharging and the occurrence of wrinkles and cracks in the current collector 11 are further suppressed, and the cycle life is further improved.
[0038] The skeleton forming agent 14 of the present embodiment may contain a surfactant. This improves the lyophilicity of the skeleton forming agent 14 into the first negative electrode material 12, and the skeleton forming agent 14 uniformly penetrates into the negative electrode material 12. Therefore, a uniform skeleton is formed between the negative electrode active materials 13 in the negative electrode material 12, and the cycle life characteristics are further improved.
[0039] In this embodiment, the content (density) of the framework forming agent 14 relative to the total of the first negative electrode material 12 and the second negative electrode material 19 is 0.5 to 2.0 mg / cm 2 When the content of the skeletal former 14 relative to the total content of the first negative electrode material and the second negative electrode material is within this range, the above-mentioned effects of using the skeletal former 14 are more reliably exhibited.
[0040] When the total solid content of the negative electrode active material 13, the skeletal former 14, the conductive assistant 15, and the binder 16 is taken as 100 mass%, the content of the skeletal former 14 is preferably 3.0 to 40.0 mass%. If the content of the skeletal former 14 is within this range, the above-mentioned effect of using the skeletal former 14 is more reliably exhibited. By making the content of the skeletal former 14 in the total solid content of the negative electrode active material 13, the skeletal former 14, the conductive assistant 15, and the binder 16 3.0 mass% or more, the function of the skeletal former 14 can be more fully obtained. In addition, by making the content of the skeletal former 14 40.0 mass% or less, the decrease in energy density can be more effectively prevented. The content of the skeletal former 14 is more preferably 5.0 to 30.0 mass%.
[0041] Here, in the negative electrode 1 for a nonaqueous electrolyte secondary battery of this embodiment, the skeletal former 14 is disposed at least at the interface between the current collector 11 and the first negative electrode material 12 and the second negative electrode material 19, and in the pores of the current collector 11. More specifically, the skeletal former 14 is disposed uniformly not only at the interface between the current collector 11 and the negative electrode material 12, but also throughout the current collector 11 and the first negative electrode material 12, and is present in a dispersed state between the negative electrode active materials 13. In contrast, in a conventional negative electrode for a nonaqueous electrolyte secondary battery, the skeletal former is unevenly distributed on the surface of the negative electrode material.
[0042] The negative electrode 1 for lithium ion secondary batteries according to this embodiment includes a conductive assistant 15 in the first region 17. The conductive assistant 15 is not particularly limited as long as it has electronic conductivity, and metals, carbon materials, conductive polymers, conductive glass, and the like can be used. Specific examples include acetylene black (AB), ketjen black (KB), furnace black (FB), thermal black, lamp black, channel black, roller black, disc black, carbon black (CB), carbon fiber (e.g., vapor-grown carbon fiber VGCF (registered trademark)), carbon nanotubes (CNT), carbon nanohorns, graphite, graphene, glassy carbon, amorphous carbon, and the like, and one or more of these can be used.
[0043] When the total of the negative electrode active material 13, the conductive assistant 15, and the binder 16 contained in the first negative electrode material 12 is taken as 100 mass%, the content of the conductive assistant 15 is preferably 0 to 20.0 mass%. If the content of the conductive assistant 15 is within this range, the conductivity can be improved without decreasing the negative electrode capacity density, and voids capable of retaining a sufficient amount of the skeleton forming agent 14 can be formed inside the first negative electrode material 12. The content of the conductive assistant 15 is more preferably 8.8 to 25.0 mass%.
[0044] The conductive assistant 15 of this embodiment has a bulk density of 0.04 to 0.25 mg / cm 3 When the bulk density of the conductive assistant 15 is within this range, the above-mentioned skeletal forming agent 14 can be sufficiently impregnated, and the above-mentioned effect of the skeletal forming agent 14 can be fully exhibited. A more preferable bulk density of the conductive assistant 15 is 0.04 to 0.15 mg / cm. 3 It is.
[0045] The negative electrode 1 for a lithium ion secondary battery according to this embodiment includes a binder 16 in the first region 17. Examples of the binder 16 include polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), polyimide (PI), polyamide, polyamideimide, aramid, polyacrylic, styrene butadiene rubber (SBR), ethylene-vinyl acetate copolymer (EVA), styrene-ethylene-butylene-styrene copolymer (SEBS), carboxymethyl cellulose (CMC), xanthan gum, polyvinyl alcohol (PVA), ethylene vinyl alcohol, polyvinyl butyral (PVB), ethylene vinyl alcohol, polyethylene (PE), polypropylene (PP), polyacrylic acid, lithium polyacrylate, sodium polyacrylate, potassium polyacrylate, ammonium polyacrylate, methyl polyacrylate, ethyl polyacrylate, amine polyacrylate, ethylene polyacrylate, and the like. Organic materials such as ester, epoxy resin, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), nylon, vinyl chloride, silicone rubber, nitrile rubber, cyanoacrylate, urea resin, melamine resin, phenolic resin, latex, polyurethane, silylated urethane, nitrocellulose, dextrin, polyvinylpyrrolidone, vinyl acetate, polystyrene, chloropropylene, resorcinol resin, polyaromatic, modified silicone, methacrylic resin, polybutene, butyl rubber, 2-propenoic acid, cyanoacrylic acid, methyl methacrylate, glycidyl methacrylate, acrylic oligomer, 2-hydroxyethyl acrylate, alginic acid, starch, lacquer, sucrose, glue, casein, and cellulose nanofibers may be used alone or in combination of two or more.
[0046] In addition, a mixture of the above-mentioned various organic binders and inorganic binders may be used. Examples of inorganic binders include silicate-based, phosphate-based, sol-based, and cement-based binders. For example, lithium silicate, sodium silicate, potassium silicate, cesium silicate, guanidine silicate, ammonium silicate, silicofluoride, borate, lithium aluminate, sodium aluminate, potassium aluminate, aluminosilicate, lithium aluminate, sodium aluminate, potassium aluminate, polyaluminum chloride, polyaluminum sulfate, polyaluminum silicate sulfate, aluminum sulfate, aluminum nitrate, ammonium alum, lithium alum, sodium alum, potassium alum, chrome alum, iron alum, manganese alum, nickel ammonium sulfate, diatomaceous earth, polyzirconoxane, polytanthane taloxane, mullite, white carbon, silica sol, colloidal silica, fumed silica, alumina sol, colloidal alumina, fumed alumina, zirconium sol, silicic acid ... Inorganic materials such as conia sol, colloidal zirconia, fumed zirconia, magnesia sol, colloidal magnesia, fumed magnesia, calcia sol, colloidal calcia, fumed calcia, titania sol, colloidal titania, fumed titania, zeolite, silicoaluminophosphate zeolite, sepiolite, montmorillonite, kaolin, saponite, aluminum phosphate, magnesium phosphate, calcium phosphate, iron phosphate, copper phosphate, zinc phosphate, titanium phosphate, manganese phosphate, barium phosphate, tin phosphate, low melting point glass, plaster, gypsum, magnesium cement, litharge cement, Portland cement, blast furnace cement, fly ash cement, silica cement, phosphate cement, concrete, and solid electrolytes may be used alone or in combination of two or more.
[0047] In this embodiment, the negative electrode active material 13 and the skeletal forming agent 14 are firmly bonded by the above-mentioned interface layer formed by using the second negative electrode material 19 having the skeletal forming agent 14, so that all of the above-mentioned binders 16 can be used. When the total of the negative electrode active material 13, the conductive assistant 15, and the binder 16 contained in the first negative electrode material 12 is taken as 100 mass%, the content of the binder 16 is preferably 0.1 to 60 mass%. By having the content of the binder 16 within this range, it is possible to improve the ion conductivity without decreasing the negative electrode capacity density, and to obtain high mechanical strength, thereby obtaining better cycle life characteristics. The content of the binder 16 is more preferably 0.5 to 30 mass%.
[0048] The negative electrode 1 for a non-aqueous electrolyte secondary battery of this embodiment has a pair of first regions 17 (hereinafter also simply referred to as "first regions") formed on both outer sides of the current collector 11 in the thickness direction, in which the first negative electrode material 12 and the second negative electrode material 19 are arranged, and a second region 18 (hereinafter also simply referred to as "second region" or "central space layer") formed in the center of the current collector in the thickness direction, in which the first negative electrode material 12 is not arranged and the second negative electrode material 19 is arranged. With this configuration, in the manufacturing process of the negative electrode 1 for a non-aqueous electrolyte secondary battery of this embodiment in which the second negative electrode material 19 having the skeletal forming agent 14 is applied to the entire current collector 11, the skeletal forming agent 14 can permeate into the first region 17 from the first region 17 and also from the second region 18. That is, the skeletal forming agent 14 permeates sufficiently throughout the entire inside of the current collector 11. By thoroughly penetrating the framework forming agent 14 into the entire interior of the current collector 11, deterioration of the structure inside the negative electrode can be suppressed, and cycle durability can also be improved. The thickness of the second region 18, which is formed in the center in the thickness direction of the current collector and in which the first negative electrode material 12 is not arranged but the second negative electrode material 19 is arranged, is preferably 0.5 to 15% of the thickness of the entire electrode. The thickness of the second region 18 is more preferably 5 to 100 μm.
[0049] The thickness of the negative electrode 1 for a nonaqueous electrolyte secondary battery of this embodiment having the above configuration is preferably 50 μm to 1000 μm. If the thickness of the negative electrode 1 for a nonaqueous electrolyte secondary battery is within this range, durability deterioration can be suppressed and energy density can be improved compared to conventional negative electrodes. The thickness of the negative electrode 1 for a nonaqueous electrolyte secondary battery is more preferably 150 μm to 800 μm.
[0050] In the negative electrode 1 for a nonaqueous electrolyte secondary battery of this embodiment, the distance between the current collector 11 made of a porous metal body and the negative electrode active material 13 is preferably 50 μm or less. If the distance between the current collector 11 made of a porous metal body and the negative electrode active material 13 is 50 μm or less, durability deterioration can be suppressed. The distance between the current collector 11 made of a porous metal body and the negative electrode active material 13 is more preferably 30 μm or less.
[0051] [Positive electrode] Next, a positive electrode in the case where the above-mentioned negative electrode is used to construct a lithium ion secondary battery will be described. The positive electrode active material is not particularly limited as long as it is a positive electrode active material that is normally used in lithium ion secondary batteries. For example, positive electrode active materials such as alkali metal transition metal oxides, vanadium, sulfur, solid solutions (lithium excess, sodium excess, potassium excess), carbon, and organic materials can be used.
[0052] The positive electrode for a lithium ion secondary battery of this embodiment may contain a skeletal former, similar to the negative electrode described above. The skeletal former may be the same as that of the negative electrode described above, and the preferred content of the skeletal former is also the same as that of the negative electrode.
[0053] The positive electrode for lithium ion secondary battery of this embodiment may contain a conductive assistant. As the conductive assistant, the above-mentioned various conductive assistants that can be used in the negative electrode are used. The preferred content of the conductive assistant is also the same as that of the negative electrode.
[0054] The positive electrode for lithium ion secondary battery of this embodiment may contain a binder. As the binder, for example, organic materials such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), hexafluoropropylene, tetrafluoroethylene, polyacrylic, alginic acid, etc. may be used alone or in combination of two or more. In addition, these organic binders may be mixed with inorganic binders. Examples of inorganic binders include silicate-based, phosphate-based, sol-based, and cement-based binders.
[0055] The current collector used for the positive electrode is not particularly limited as long as it has electronic conductivity and can pass electricity through the positive electrode active material held therein. For example, conductive materials such as C, Ti, Cr, Ni, Cu, Mo, Ru, Rh, Ta, W, Os, Ir, Pt, Au, Al, and alloys containing two or more of these conductive materials (for example, stainless steel and Al-Fe alloy) can be used. When using a conductive material other than the above, for example, a multilayer structure of heterogeneous metals such as iron coated with Al, or heterogeneous elements such as Al coated with C may be used. From the viewpoint of high electrical conductivity and high stability in the electrolyte, C, Ti, Cr, Au, Al, stainless steel, and the like are preferred as the current collector, and further from the viewpoint of oxidation resistance and material cost, C, Al, stainless steel, and the like are preferred. More preferred are carbon-coated Al or Al alloy, and carbon-coated stainless steel.
[0056] The shape of the current collector used in the positive electrode may be linear, rod-like, plate-like, foil-like, or porous, among which the porous shape may be used since it can increase the packing density and the skeleton forming agent can easily penetrate into the active material layer. Examples of the porous shape include mesh, woven fabric, nonwoven fabric, embossed body, punched body, expanded body, and foamed body. The same porous metal body as that of the negative electrode may be used.
[0057] [Separator] In the lithium ion secondary battery of this embodiment, a separator that is generally used in lithium ion secondary batteries can be used, such as a polyethylene microporous film, a polypropylene microporous film, a glass nonwoven fabric, an aramid nonwoven fabric, a polyimide microporous film, or a polyolefin microporous film.
[0058] [Electrolyte] In the lithium ion secondary battery of this embodiment, the electrolyte may be any electrolyte that is commonly used in lithium ion secondary batteries. For example, an electrolyte solution in which an electrolyte is dissolved in a solvent, a gel electrolyte, a solid electrolyte, an ionic liquid, or a molten salt may be used. Here, the electrolyte solution refers to an electrolyte dissolved in a solvent.
[0059] The electrolyte for the lithium ion secondary battery must contain lithium ions as a carrier responsible for electrical conduction, and thus the electrolyte salt is not particularly limited as long as it is used in the lithium ion secondary battery, but a lithium salt is preferable. As the lithium salt, at least one selected from the group consisting of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium trifluoromethanesulfonate (LiCF3SO4), lithium bistrifluoromethanesulfonylimide (LiN(SO2CF3)2), lithium bispentafluoroethanesulfonylimide (LiN(SO2C2F5)2), lithium bisoxalatoborate (LiBC4O8), etc., can be used, or two or more can be used in combination.
[0060] The electrolyte solvent is not particularly limited as long as it is one that is used in lithium ion secondary batteries. For example, at least one selected from the group consisting of propylene carbonate (PC), ethylene carbonate (EC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), γ-butyrolactone (GBL), methyl-γ-butyrolactone, dimethoxymethane (DMM), dimethoxyethane (DME), vinylene carbonate (VC), vinylethylene carbonate (EVC), fluoroethylene carbonate (FEC), and ethylene sulfite (ES) can be used, or two or more of them can be used in combination.
[0061] Furthermore, the concentration of the electrolyte (concentration of the salt in the solvent) is not particularly limited, but is preferably 0.1 to 3.0 mol / L, and more preferably 0.8 to 2.0 mol / L.
[0062] Ionic liquids and molten salts are classified into pyridine-based, alicyclic amine-based, aliphatic amine-based, etc., based on the type of cation (positive ion). By selecting the type of anion (negative ion) to be combined with this, a variety of ionic liquids or molten salts can be synthesized. Examples of cations include ammonium-based ions such as imidazolium salts and pyridinium salts, phosphonium-based ions, inorganic ions, etc. Examples of anions include halogen-based ions such as bromide ions and triflates, boron-based ions such as tetraphenylborate, and phosphorus-based ions such as hexafluorophosphate.
[0063] Ionic liquids and molten salts are, for example, cations such as imidazolinium and Br - , Cl - , B.F. 4- , P.F. 6- , (CF3SO2)2N - , CF3SO 3- , FeCl 4- The electrolyte can be obtained by a known synthesis method such as combining with an anion such as the above. If it is an ionic liquid or a molten salt, it can function as an electrolyte without adding an electrolyte.
[0064] Solid electrolytes are classified into sulfide-based, oxide-based, hydride-based, organic polymer-based, etc. Most of these are amorphous or crystalline, consisting of carrier salts and inorganic derivatives. Because there is no need to use flammable aprotic organic solvents like electrolytes, there is less risk of gas or liquid application or liquid leakage, and it is expected to become a secondary battery with excellent safety.
[0065] [Manufacturing method] Next, a method for manufacturing the lithium ion secondary battery according to this embodiment will be described. The method for manufacturing a negative electrode for a lithium ion secondary battery according to the present embodiment includes a first step of forming a pair of first regions on a current collector, the first and second negative electrode materials being disposed on both outer sides of the current collector in the thickness direction, and a second region on the current collector in the center of the thickness direction, the first negative electrode material being not disposed but the second negative electrode material being disposed, and then applying a negative electrode material containing a first negative electrode material containing a negative electrode active material, a conductive additive, and a binder only to the first region and drying the coated negative electrode material to form a negative electrode layer precursor on the current collector, the pair of first regions being disposed on both outer sides of the current collector in the thickness direction, the first negative electrode material being disposed, and the second region on the current collector in the center of the thickness direction, the first negative electrode material being not disposed. FIG. 3 is an example of the first step. In the first step, for example, a nickel porous material having a thickness of 1000 μm is manufactured, and a nickel porous body wound in advance in a roll shape is prepared. Meanwhile, a negative electrode active material, a binder, a conductive assistant, etc. are mixed with N-methyl-2-pyrrolidone as a negative electrode material containing a first negative electrode material to prepare a slurry of a negative electrode material containing a paste-like first negative electrode material. From the viewpoint of the coating property and filling property to the porous material, the viscosity of the prepared negative electrode material slurry containing the first negative electrode material is preferably 5,000 to 30,000 mPa·s. Next, the inside of the nickel porous body is filled and coated with the slurry-like negative electrode material using a coater 21, dried, and then pressure-adjusted to obtain a negative electrode layer precursor.
[0066] As described above, the negative electrode layer precursor may be left in a wet state without being dried. In addition to the above-mentioned slurry coating, for example, a method of forming a negative electrode active material layer inside a porous current collector by using a chemical plating method, a sputtering method, a vapor deposition method, a gas deposition method, a dipping method, etc., of the negative electrode active material (precursor) and integrating it is possible to use such a method. However, from the viewpoint of the lyophilicity of the framework forming agent and the electrode manufacturing cost, the slurry filling coating method or the dipping method is preferable.
[0067] The method for producing a negative electrode for a lithium ion secondary battery according to the present embodiment includes a second step of impregnating the negative electrode layer precursor formed in the first step with a solution 22 containing a second negative electrode material having a skeleton-forming agent containing a silicate having a siloxane bond or a phosphate having a phosphate bond, and drying the solution to harden the skeleton-forming agent and form a skeleton of the negative electrode active material layer. For example, a silicate having a siloxane bond or a phosphate having a phosphate bond is purified by a dry or wet method, and then water is added to adjust the solution to prepare a solution of a negative electrode material containing a second negative electrode material containing a skeleton-forming agent (skeleton-forming agent solution). At this time, a surfactant may be mixed. As a dry method, for example, SiO2 is added to water in which an alkali metal hydroxide is dissolved, and the mixture is treated in an autoclave at 150°C to 250°C to produce an alkali metal silicate. As a wet method, for example, a mixture of an alkali metal carbonate compound and SiO2 is fired at 1000°C to 2000°C, and then the mixture is dissolved in hot water to produce the alkali metal silicate. FIG. 4 is an illustration of the second step.
[0068] Next, the surface of the negative electrode layer precursor is coated with a skeleton-forming agent liquid to coat the negative electrode active material. The skeleton-forming agent can be applied by impregnating the negative electrode layer precursor into a tank containing the skeleton-forming agent liquid, or by dripping or applying the skeleton-forming agent onto the surface of the negative electrode layer precursor, spray coating, screen printing, curtain printing, spin coating, gravure coating, die coating, or the like. The skeleton-forming agent applied to the surface of the negative electrode layer precursor penetrates into the inside of the negative electrode and enters into the gaps between the negative electrode active material and the first conductive assistant. Then, the skeleton-forming agent is dried by heat treatment to harden the skeleton-forming agent. As a result, the skeleton-forming agent forms the skeleton of the negative electrode active material layer.
[0069] A preferred method of applying the skeleton-forming agent to the negative electrode layer precursor of this embodiment is to impregnate the entire negative electrode layer precursor with the skeleton-forming agent liquid and apply the agent so that the entire second region is impregnated with the skeleton-forming agent liquid. It is presumed that the capillary phenomenon occurs when the negative electrode layer precursor is impregnated in a tank of the skeleton-forming agent liquid, and the skeleton-forming agent is more likely to penetrate from the second region to the first region. A more preferred application method is to impregnate the entire negative electrode layer precursor with the skeleton-forming agent liquid from the surface where the cross-sectional area of the second region is the smallest. It is presumed that this is because the action of the capillary phenomenon is maximized. Incidentally, it is preferable that the framework-forming agent liquid adhering to the surface of the negative electrode layer precursor after the impregnation is removed as an excess.
[0070] The heat treatment is preferably performed at 80°C or higher, more preferably 100°C or higher, and desirably 110°C or higher, because a higher temperature can shorten the heat treatment time and improve the strength of the skeleton-forming agent. The upper limit temperature of the heat treatment is not particularly limited as long as the current collector does not melt, and may be increased to, for example, about 1000°C, which is the melting point of copper. In the case of conventional electrodes, the binder may carbonize or the current collector may soften, so the upper limit temperature was estimated to be much lower than 1000°C. However, in this embodiment, the skeleton-forming agent is used, and the skeleton-forming agent exhibits excellent heat resistance and is stronger than the strength of the current collector, so the upper limit temperature is 1000°C.
[0071] The heat treatment can be performed for a period of 0.5 to 100 hours. The heat treatment may be performed in air, but is preferably performed in a non-oxidizing atmosphere to prevent oxidation of the current collector.
[0072] In the method for producing a negative electrode for a lithium ion secondary battery according to the present embodiment, the ratio B / A of the density B of the negative electrode layer formed in the second step to the density A of the negative electrode layer precursor formed in the first step is 0.9 or less.
[0073] In the method for producing a negative electrode for a lithium ion secondary battery according to the present embodiment, the density A of the negative electrode layer precursor formed in the first step is set to 0.5 to 2.0 g / cm 3 This makes it possible to more reliably set the ratio B / A of the density B of the negative electrode layer to the density A of the negative electrode layer precursor (i.e., density increase ratio) within the above range, thereby enhancing the effect of the above-mentioned framework forming agent. A more preferable range for the density A of the negative electrode layer precursor is 0.6 to 1.5 g / cm 3 The density A of the negative electrode layer precursor is 0.6 g / cm 3 By setting the electrode density at 1.5 g / cm or more, it is possible to suppress the decrease in energy density due to the decrease in electrode density. 3 The capacity reduction can be suppressed by setting the following.
[0074] The positive electrode for lithium ion secondary battery of the present invention has a process for producing a positive electrode by coating a positive electrode material containing a positive electrode active material, a conductive assistant, and a binder on a current collector, drying and rolling the positive electrode material. For example, a rolled aluminum foil having a thickness of 10 μm is produced, and the aluminum foil is prepared in advance in a roll shape, while a positive electrode material is prepared by mixing a positive electrode active material, a binder, a conductive assistant, etc. to prepare a paste-like slurry. Next, the slurry-like positive electrode material is coated on the surface of the aluminum, dried, and then a roll press process is performed to obtain a positive electrode. In addition, a foamed porous body made of metal may be used as the current collector. The current collector is characterized in that the electrode mixture is filled. The method for filling the electrode mixture into the current collector is not particularly limited, but for example, a method of filling the inside of the mesh structure of the current collector with a slurry containing the electrode mixture by applying pressure by a pressing method can be mentioned. After filling the electrode mixture, the filled current collector is dried and then pressed to improve the density of the electrode mixture and adjust it to a desired density.
[0075] Finally, the obtained negative electrode and positive electrode are cut to a desired size, joined together with a separator therebetween, and sealed in an electrolyte to obtain a lithium ion secondary battery. The structure of the lithium ion secondary battery can be applied to existing battery forms and structures such as stacked batteries and wound batteries.
[0076] [effect] According to this embodiment, the following effects are achieved. In this embodiment, a negative electrode for a nonaqueous electrolyte secondary battery is configured, comprising: a current collector 11 formed of a porous metal body; a current collector 11 formed of a porous metal body; a negative electrode active material 13 arranged in the pores of the porous metal body and composed of a silicon-based material; a first negative electrode material 12 having a conductive assistant 15 and a binder 16; and a second negative electrode material 19 arranged in the pores of the porous metal body and having a framework forming agent 14 including a silicate having a siloxane bond. The negative electrode has a pair of first regions 17 formed on both outer sides in the thickness direction of the current collector 11 and in which the first negative electrode material and the second negative electrode material are arranged; and a second region 18 formed in the center in the thickness direction of the current collector and in which the first negative electrode material is not arranged but the second negative electrode material is arranged.
[0077] First, by using a porous metal body as the current collector 11, it becomes possible to fix the first negative electrode material 12 in the micron-sized region by the porous metal skeleton, and peeling and cracking of the negative electrode can be suppressed. Furthermore, by using the second negative electrode material 19 having the skeletal forming agent 14, it becomes possible to fix the first negative electrode material 12 in the nano-sized region. More specifically, the third phase is formed by the skeletal forming agent 14 at the interface between the current collector 11 made of a porous metal body and the negative electrode active material 13, and the negative electrode active material 13 is firmly bound within the first negative electrode material 12, thereby preventing it from falling off during expansion and contraction, and preventing structural deterioration of the electrode. Furthermore, the current collector 11 has a pair of first regions 17 formed on both outer sides in the thickness direction of the current collector, in which a first negative electrode material and a second negative electrode material are arranged, and a second region 18 in which the first negative electrode material is not arranged and the second negative electrode material is arranged. This allows the second negative electrode material 19 having the skeletal forming agent 14 to permeate from the first region 17 into the inside of the current collector 11, and also from the second region 18 into the first region 17. In other words, the second negative electrode material 19 having the skeletal forming agent 14 can sufficiently permeate the entire inside of the current collector 11, so that deterioration of the negative electrode structure is suppressed and cycle durability can be improved. Therefore, by having the first region 17 and the second region 18 in the current collector 11, the second negative electrode material 19 having the framework forming agent 14 can sufficiently permeate the entire inside of the negative electrode, so that even if the negative electrode uses the negative electrode active material 13 composed of a silicon-based material having a high capacity and an extremely large expansion and contraction rate, the negative electrode structure can be maintained even when full charge and discharge cycles are performed with an SOC of 0 to 100. Furthermore, since it is possible to suppress the deterioration of the negative electrode structure caused by the increase in capacity due to the thickening of the negative electrode film and the dropout and breakage of the conductive path at a high basis weight, it is possible to achieve high cycle durability.
[0078] Second Embodiment In addition, as another embodiment of the negative electrode for a nonaqueous electrolyte secondary battery of the present invention, a configuration (hereinafter also referred to as a second embodiment) including a current collector made of a porous metal body, a first negative electrode material arranged in the pores of the porous metal body and having a conductive assistant, a second negative electrode material arranged in the pores of the porous metal body and having a negative electrode active material composed of a silicon-based material, a conductive assistant and a binder, and a third negative electrode material arranged in the pores of the porous metal body and having a framework forming agent containing a silicate having a siloxane bond, the first negative electrode material, the second negative electrode material and the third negative electrode material are arranged on both outer sides of the current collector in the thickness direction, and a pair of first regions in which the first negative electrode material, the second negative electrode material and the third negative electrode material are arranged, and a second region formed in the center of the current collector in the thickness direction, in which the second negative electrode material is not arranged and the first negative electrode material and the third negative electrode material are arranged will be described in detail with reference to the drawings.
[0079] [Negative electrode] As shown in FIG. 2, the negative electrode 1a for a nonaqueous electrolyte secondary battery according to this embodiment comprises a current collector 11 made of a porous metal body, a first negative electrode material 12a disposed in the pores of the porous metal body and having a conductive assistant 15, a second negative electrode material 19a disposed in the pores of the porous metal body and having a negative electrode active material 13 made of a silicon-based material, the conductive assistant 15, and a binder 16, and a third negative electrode material 20 disposed in the pores of the porous metal body and having a framework forming agent 14 including a silicate having a siloxane bond. The negative electrode 1a for a nonaqueous electrolyte secondary battery according to this embodiment has a pair of first regions 17a formed on both outer sides of the current collector 11 in the thickness direction of the current collector 11, and in which a first negative electrode material 12a, a second negative electrode material 19a, and a third negative electrode material 20 are arranged, and a second region 18a formed in the center of the current collector in the thickness direction, in which the second negative electrode material 19a is not arranged, and in which the first negative electrode material 12a and the third negative electrode material 20 are arranged. For example, by applying this embodiment to a negative electrode for a lithium ion secondary battery, the permeability of the framework forming agent into the inside of a current collector made of a porous metal body can be further improved, thereby making it possible to provide a negative electrode for a lithium ion secondary battery that can better suppress deterioration of the electrode structure and further improve cycle durability, and a lithium ion secondary battery including the same. Below, an example in which this embodiment is applied to a negative electrode for a lithium ion secondary battery will be described in detail, but various additions, modifications, and deletions are possible within the scope of the present invention.
[0080] In the negative electrode 1a for a non-aqueous electrolyte secondary battery of this embodiment, the current collector 11 has a pair of first regions 17a (hereinafter also simply referred to as "first regions") formed on both outer sides in the thickness direction of the current collector 11 and in which the first negative electrode material 12a, the second negative electrode material 19a, and the third negative electrode material 20 are arranged, and a second region 18a (hereinafter also simply referred to as "second region" or "central space layer") formed in the center in the thickness direction of the current collector and in which the first negative electrode material 12a and the third negative electrode material 20 are arranged without the second negative electrode material 19a being arranged. With this configuration, in the manufacturing process of the negative electrode 1a for a non-aqueous electrolyte secondary battery of this embodiment, in which the third negative electrode material 20 having the skeletal forming agent 14 is applied to the entire current collector 11, the skeletal forming agent 14 can permeate into the first region 17a from the first region 17a as well as from the second region 18a. That is, the framework-forming agent 14 sufficiently permeates the entire interior of the current collector 11. By allowing the framework-forming agent 14 to sufficiently permeate the entire interior of the current collector 11, deterioration of the structure inside the negative electrode can be further suppressed, and cycle durability can also be further improved. The thickness of the second region 18a, which is formed in the center in the thickness direction of the current collector and in which the second negative electrode material 19a is not arranged but the first negative electrode material 12a and the third negative electrode material 20 are arranged, is preferably 0.5 to 15% of the thickness of the entire electrode. More preferably, the thickness of the second region 18a is 5 to 100 μm.
[0081] In this embodiment, it is preferable that the first negative electrode material 12a having the conductive assistant 15 is present in the first region 17a and the second region 18a of the current collector 11. As the conductive assistant 15 contained as the first negative electrode material 12a in this embodiment, the conductive assistant 15 in the first embodiment can be preferably a fibrous carbon material or a material having a DBP (dibutyl phthalate) oil absorption of 200 ml / g or more as specified in JIS K 6217-4. The conductive assistant 15 having the above properties is porous, has a high specific surface area, and has high liquid absorption. When the third negative electrode material 20 having the skeletal forming agent 14 is applied to the current collector (negative electrode layer precursor) containing such a conductive assistant 15, the third negative electrode material 20 having the skeletal forming agent 14 exhibits higher liquid absorption than when the second negative electrode material having the skeletal forming agent 14 is applied to the current collector (negative electrode layer precursor) of the first embodiment. It is presumed that this is because the inclusion of the conductive assistant 15 in the current collector causes a stronger capillary phenomenon, which further improves the dispersibility and permeability of the third negative electrode material 20 having the skeletal forming agent 14 throughout the inside of the current collector 11. Specific examples of the conductive assistant 15 that may be included in the first negative electrode material of the present embodiment include acetylene black (AB), ketjen black (KB), furnace black (FB), thermal black, lamp black, channel black, roller black, disc black, carbon black (CB), carbon fiber (e.g., vapor grown carbon fiber VGCF (registered trademark)), carbon nanotubes (CNT), carbon nanohorns, graphite, graphene, glassy carbon, amorphous carbon, and the like, and one or more of these can be used.
[0082] The weight of the conductive assistant 15 in the first negative electrode material is 0.1 to 1.0 mg / cm 2When the content of the conductive assistant 15 in the first negative electrode material is within this range, the above-mentioned effects of the conductive assistant 15 are more reliably exhibited.
[0083] In addition, when the total of the negative electrode active material 13, the conductive assistant 15, and the binder 16 contained in the first negative electrode material 12a and the second negative electrode material 19a is taken as 100 mass%, the content of the conductive assistant 15 in the first negative electrode material 12a and the second negative electrode material 19a is preferably 0 to 20.0 mass%. If the total content of the conductive assistant 15 is within this range, the conductivity can be improved without decreasing the negative electrode capacity density, voids capable of retaining a sufficient amount of the skeleton-forming agent 14 can be formed inside the current collector 11, and the permeability of the skeleton-forming agent into the inside of the current collector is improved by capillary action.
[0084] The conductive assistant 15 of this embodiment has a bulk density of 0.04 to 0.25 mg / cm 3 When the bulk density of the conductive assistant 15 is within this range, the third negative electrode material 20 having the above-mentioned skeletal forming agent 14 can be sufficiently impregnated into the current collector 11 by capillary action, and the effect of the above-mentioned skeletal forming agent 14 can be fully exhibited. A more preferable bulk density of the conductive assistant 15 is 0.04 to 0.15 mg / cm. 3 It is.
[0085] The content (density) of the framework forming agent 14 relative to the total of the first negative electrode material 12a, the second negative electrode material 19a, and the third negative electrode material 20 is 0.5 to 2.0 mg / cm 2 When the content of the skeletal former 14 relative to the total of the first negative electrode material 12a, the second negative electrode material 19a, and the third negative electrode material 20 is within this range, the above-mentioned effect of using the skeletal former 14 is more reliably exhibited.
[0086] When the total solid content of the negative electrode active material 13, the skeletal former 14, the conductive assistant 15, and the binder 16 contained in the first negative electrode material 12a, the second negative electrode material 19a, and the third negative electrode material 20 is taken as 100 mass%, the content of the skeletal former 14 is preferably 3.0 to 40.0 mass%. If the content of the skeletal former 14 is within this range, the above-mentioned effect of using the skeletal former 14 is more reliably exhibited. By making the content of the skeletal former 14 in the negative electrode material 12 3.0 mass% or more, the function of the skeletal former 14 can be more fully obtained. In addition, by making the content of the skeletal former 14 40.0 mass% or less, the decrease in energy density can be more effectively prevented. The content of the skeletal former 14 is more preferably 5.0 to 30.0 mass%.
[0087] In this embodiment, the negative electrode active material 13 and the skeletal forming agent 14 are firmly bonded by the above-mentioned interface layer formed by using the third negative electrode material 20 having the skeletal forming agent 14, so all of the binders 16 in the first embodiment can be used. When the total of the negative electrode active material 13, the conductive assistant 15, and the binder 16 contained in the first negative electrode material 12a and the second negative electrode material 19a is taken as 100 mass%, the content of the binder 16 is preferably 0.1 to 60 mass%. By having the content of the binder 16 within this range, it is possible to improve the ion conductivity without decreasing the negative electrode capacity density, and to obtain high mechanical strength, thereby obtaining better cycle life characteristics. The content of the binder 16 is more preferably 0.5 to 30 mass%.
[0088] [Manufacturing method] Next, a method for manufacturing the lithium ion secondary battery according to this embodiment will be described. The method for producing a negative electrode for a lithium ion secondary battery according to this embodiment includes a first step of forming a conductive path in a current collector by applying a conductive agent solution containing a first negative electrode material having a conductive assistant to the current collector and drying the applied solution. For example, a nickel porous material having a thickness of 1000 μm is manufactured, and a nickel porous body wound in a roll shape is prepared in advance, while a conductive agent solution containing a first negative electrode material is prepared by dissolving or dispersing a conductive agent in N-methyl-2-pyrrolidone. Next, the conductive agent solution containing the first negative electrode material is filled and applied inside the nickel porous body, and after drying, a pressure adjustment process is performed to obtain a negative electrode layer precursor. As described above, the negative electrode layer precursor may be left in a wet state without being dried. In addition, the conductive agent solution containing the first negative electrode material having a conductive agent can be applied by a method of dropping and applying the conductive agent solution on the surface of a current collector, spray coating, screen printing, curtain method, spin coating, gravure coating, die coating, etc., in addition to the above-mentioned slurry coating. However, from the viewpoint of electrode manufacturing costs, a slurry filling coating method or a dipping method is preferable.
[0089] The method for producing a negative electrode for a lithium ion secondary battery according to this embodiment includes a second step of forming a negative electrode layer precursor on the negative electrode layer precursor formed in the first step in the same manner as in the first embodiment, the negative electrode layer precursor having a pair of first regions formed on both outer sides of the current collector in the thickness direction and in which a first negative electrode material and a second negative electrode material are arranged, and a second region formed in the center of the current collector in the thickness direction and in which the first negative electrode material is arranged without the second negative electrode material being arranged. Fig. 5 is a schematic diagram of the first step and the second step according to this embodiment. As the second step of the manufacturing method of this embodiment, the first step of the first embodiment can be preferably used within the scope of this embodiment. Also, for the parts not described in detail, the configuration and method of the first embodiment can be preferably used within the scope of this embodiment.
[0090] The method for producing a negative electrode for a lithium ion secondary battery according to this embodiment includes a third step of impregnating the negative electrode layer precursor formed in the second step with a solution 22a containing a negative electrode material including a third negative electrode material having a skeleton-forming agent, and drying the solution, thereby hardening the skeleton-forming agent and forming a skeleton of the negative electrode active material layer, in the same manner as in the second step of the first embodiment. Fig. 6 is a schematic diagram of the third step of this embodiment. As the third step of the manufacturing method of this embodiment, the second step of the first embodiment can be preferably used within the scope of this embodiment. Also, for the parts not described in detail, the configuration and method of the first embodiment can be preferably used within the scope of this embodiment. The same applies to a suitable coating method for the skeleton forming agent. In addition, in this embodiment, a nonaqueous electrolyte secondary battery including the negative electrode for a nonaqueous electrolyte secondary battery according to this embodiment and the positive electrode for a nonaqueous electrolyte secondary battery produced in the first embodiment can be manufactured.
[0091] [effect] According to this embodiment, the following effects are achieved. In this embodiment, the current collector is provided with a current collector formed of a porous metal body, a first negative electrode material disposed in the pores of the porous metal body and having a conductive assistant, a second negative electrode material disposed in the pores of the porous metal body and having a negative electrode active material constituted by a silicon-based material, a conductive assistant and a binder, and a third negative electrode material disposed in the pores of the porous metal body and having a framework forming agent including a silicate having a siloxane bond. The current collector has a pair of first regions formed on both outer sides in the thickness direction of the current collector and in which the first negative electrode material, the second negative electrode material and the third negative electrode material are disposed, and a second region formed in the center in the thickness direction of the current collector and in which the second negative electrode material is not disposed and the first negative electrode material and the third negative electrode material are disposed.
[0092] In this embodiment, the first region, which is formed on both outer sides of the current collector 11 in the thickness direction and in which the first negative electrode material, the second negative electrode material, and the third negative electrode material are arranged, and the second region, which is formed in the center of the current collector in the thickness direction and in which the first negative electrode material and the third negative electrode material 20 are arranged without the second negative electrode material arranged, contain the first negative electrode material having the conductive assistant 15, so that the skeleton-forming agent 14 can penetrate more effectively from the second region 18 into the first region 17 by capillary action than the skeleton-forming agent 14 penetrates into the first region 17. In other words, the skeleton-forming agent 14 can penetrate more effectively and thoroughly into the entire inside of the current collector 11, so that the structural deterioration of the negative electrode is better suppressed and the cycle durability can be better improved. Therefore, by adopting the configuration of the second embodiment, the framework forming agent 14 not only permeates into the first region 17, but also the framework forming agent 14 can permeate from the second region 18 into the first region 17 by capillary action. Therefore, even when a full charge / discharge cycle with an SOC of 0 to 100 is performed, the negative electrode structure can be maintained better, despite the use of the negative electrode active material 13 composed of a silicon-based material with a high capacity and an extremely large expansion / contraction rate. Furthermore, the negative electrode structure deterioration caused by the increase in capacity due to the thickening of the negative electrode film and the dropout and breakage of the conductive path at the time of a high basis weight can be suppressed better, and high cycle durability can be realized better.
[0093] The present invention is not limited to the above embodiment, and modifications and improvements within the scope of the present invention that can achieve the object of the present invention are included in the present invention. For example, a non-aqueous electrolyte secondary battery is a secondary battery (electricity storage device) that uses a non-aqueous electrolyte such as an organic solvent as the electrolyte, and includes sodium ion secondary batteries, potassium ion secondary batteries, magnesium ion secondary batteries, calcium ion secondary batteries, etc. in addition to lithium ion secondary batteries. Also, a lithium ion secondary battery means a secondary battery of a non-aqueous electrolyte that does not contain water as a main component, and a battery in which lithium ions are contained in the carrier responsible for electrical conduction. For example, lithium ion secondary batteries, metal lithium batteries, lithium polymer batteries, all-solid-state lithium batteries, air lithium ion batteries, etc. are included. The same applies to other secondary batteries. Here, a non-aqueous electrolyte that does not contain water as a main component means that the main component in the electrolyte is not water. That is, it is a known electrolyte used in a non-aqueous electrolyte secondary battery. This electrolyte can function as a secondary battery even if it contains some water, but it is desirable that the electrolyte contains as little water as possible because it adversely affects the cycle characteristics, storage characteristics, and input / output characteristics of the secondary battery. In reality, it is preferable that the water in the electrolyte is 5000 ppm or less. EXAMPLES
[0094] Next, examples of the present invention will be described, but the present invention is not limited to these examples. <Example 1> [Preparation of negative electrode] A slurry of a negative electrode material containing a first negative electrode material containing silicon (particle diameter 1 to 3 μm) as a negative electrode active material, a conductive assistant shown in Table 1, and polyvinylidene fluoride (PVdF) as a binder was prepared. Next, the prepared slurry was filled into a pair of first regions formed on both outer sides in the thickness direction of a current collector of "Nickel Celmet" (registered trademark) manufactured by Sumitomo Electric Industries, Ltd. At this time, a second region having a width of 50 μm was provided in the center of the current collector. After that, drying and pressure adjustment treatment were performed to obtain a negative electrode layer precursor having a pair of first regions formed on both outer sides in the thickness direction of the current collector and in which the first negative electrode material is arranged, and a second region formed in the center of the thickness direction of the current collector and in which the first negative electrode material is not arranged.
[0095] On the other hand, a 10 mass% aqueous solution of Na2O·3SiO2 was prepared as a skeleton-forming agent solution containing a second negative electrode material containing a skeleton-forming agent and water. The negative electrode layer precursor obtained above was immersed in the prepared skeleton-forming agent solution. After immersion, the negative electrode precursor was heated at 160°C and dried to obtain a negative electrode of Example 1, which has a pair of first regions formed on both outer sides of the current collector in the thickness direction and in which the first negative electrode material and the second negative electrode material are arranged, and a second region formed in the center of the current collector in the thickness direction and in which the first negative electrode material is not arranged and the second negative electrode material is arranged.
[0096] [Preparation of positive electrode] As the positive electrode active material, LiNi 0.5 Co 0.2 Mn 0.3 A positive electrode mixture slurry was prepared by mixing 94% by mass of the positive electrode active material, 4% by mass of carbon black as a conductive assistant, and 2% by mass of polyvinylidene fluoride (PVdF) as a binder, and dispersing the mixture in an appropriate amount of N-methyl-2-pyrrolidone (NMP). A current collector with a thickness of 1.0 mm, porosity of 95%, number of cells of 46 to 50 per inch, pore size of 0.5 mm, and specific surface area of 5000 m was used. 2 / m 3 The prepared positive electrode mixture slurry was applied by the press-in method to a coating amount of 90 mg / cm2. 2The mixture was dried in a vacuum at 120° C. for 12 hours, and then roll pressed at a pressure of 15 tons to produce a positive electrode for a lithium ion secondary battery in which the pores of the foamed aluminum were filled with the electrode mixture.
[0097] [Preparation of lithium-ion secondary batteries] A microporous membrane having a thickness of 25 μm and a three-layer laminate of polypropylene / polyethylene / polypropylene was prepared as a separator, and punched out to a size of 100 mm length × 90 mm width. The positive electrode for lithium ion secondary battery and the negative electrode for lithium ion secondary battery obtained above were stacked in the order of positive electrode / separator / negative electrode / separator / positive electrode / negative electrode to produce an electrode laminate.
[0098] Then, a tab lead was ultrasonically welded to the current collecting area of each electrode. The electrode laminate with the welded tab lead was inserted into a bag-shaped aluminum laminate for secondary batteries that was heat sealed to produce a laminate cell. As an electrolyte, a solution was prepared by dissolving 1.2 moles of LiPF6 in a solvent that was a mixture of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 3:4:3, and this solution was injected into the laminate cell to produce a lithium ion secondary battery.
[0099] <Example 2> A slurry containing furnace black was prepared as a conductive solution containing a first negative electrode material having a conductive assistant, and was filled into the entirety of "Nickel Celmet" (registered trademark) manufactured by Sumitomo Electric Industries, Ltd., which was used as a current collector, and was dried and subjected to a pressure adjustment treatment. Next, similarly to Example 1, a slurry of a negative electrode material containing a second negative electrode material containing silicon (particle diameter 1 to 3 μm) as a negative electrode active material, a conductive assistant shown in Table 1, and polyvinylidene fluoride (PVdF) as a binder was prepared, and was filled into a pair of first regions formed on both outer sides of the current collector in the thickness direction of the "Nickel Celmet" (registered trademark) manufactured by Sumitomo Electric Industries, Ltd., which was used as a current collector. At this time, a second region having a width of 50 μm was provided in the center of the current collector. Thereafter, drying and pressure adjustment treatment were performed to obtain a negative electrode layer precursor, which had a pair of first regions formed on both outer sides of the current collector in the thickness direction, in which a first negative electrode material and a second negative electrode material were arranged, and a second region formed in the center of the current collector in the thickness direction, in which the second negative electrode material was not arranged and the first negative electrode material was arranged.
[0100] The above-mentioned negative electrode layer precursor was immersed in a skeleton-forming agent liquid (corresponding to the third negative electrode material) prepared by the same procedure as in Example 1, and then the negative electrode precursor was heated at 160°C and dried to obtain a negative electrode of Example 2, which has, as a negative electrode layer, a pair of first regions formed on both outer sides in the thickness direction of the current collector and in which the first negative electrode material, the second negative electrode material, and the third negative electrode material are arranged, and a second region formed in the center in the thickness direction of the current collector and in which the second negative electrode material is not arranged and the first negative electrode material and the third negative electrode material are arranged.
[0101] In addition, the positive electrode of Example 2 had a coating amount of 45 mg / cm2 of Example 1. 2 Except for the above change, the battery was fabricated in the same manner as in Example 1. The battery was fabricated in the same manner as in Example 1.
[0102] <Comparative Example 1> A negative electrode was prepared in the same manner as in Examples 1 and 2, except that no non-filled region (central space layer) of the negative electrode material was provided during preparation of the negative electrode, i.e., the negative electrode material was applied to the entire current collector.
[0103] The positive electrode of Comparative Example 1 had a coating amount of 45 mg / cm2 2 Except for the above change, the battery was fabricated in the same manner as in Example 1. The battery was fabricated in the same manner as in Example 1.
[0104] [Aging test] An aging test was carried out on each of the Examples and Comparative Examples. The aging test was carried out at a test environment temperature of 25°C.
[0105] [Durability test] A cycle life test was carried out for each of the Examples and Comparative Examples. The cycle life test was carried out at a test environment temperature of 25° C., a current density of 0.2 C-rate, and a cutoff potential of 2.5 to 4.2 V.
[0106] [Table 1]
[0107] FIG. 7 is a diagram showing the relationship between the number of cycles and the discharge capacity in Examples 1 and 2 and Comparative Example 1. As is clear from FIG. 7, it was confirmed that this example provides a negative electrode for a nonaqueous electrolyte secondary battery capable of suppressing deterioration of the electrode structure and improving cycle durability, and a nonaqueous electrolyte secondary battery including the same. [Explanation of symbols]
[0108] 1, 1a Negative electrode for non-aqueous electrolyte secondary batteries 11 Current collector 101, 201, 202 Negative electrode layer precursor 12, 12a First negative electrode material 13 Negative electrode active material 14 Skeleton-forming agents 15 Conductive additives 16 Binder 17, 17a First Area 18, 18a Second Area 19, 19a Second anode material 20 Third anode material
Claims
1. A current collector made of a porous metal body; a first negative electrode material disposed in the pores of the porous metal body and having a negative electrode active material made of a silicon-based material, a conductive assistant, and a binder; a second negative electrode material disposed in the pores of the porous metal body and having a framework forming agent including a silicate having a siloxane bond; a pair of first regions formed on both outer sides in a thickness direction of the current collector, in which the first negative electrode material and the second negative electrode material are disposed; a second region formed in a center in a thickness direction of the current collector, in which the first negative electrode material is not disposed but the second negative electrode material is disposed.
2. A current collector made of a porous metal body; A first negative electrode material disposed in the pores of the porous metal body and having a conductive assistant; A second negative electrode material is disposed in the pores of the porous metal body and has a negative electrode active material composed of a silicon-based material and a binder; a third negative electrode material disposed in the pores of the porous metal body and having a framework forming agent including a silicate having a siloxane bond; a pair of first regions formed on both outer sides in a thickness direction of the current collector, in which the first negative electrode material, the second negative electrode material, and the third negative electrode material are disposed; a second region formed in a center in a thickness direction of the current collector, in which the second negative electrode material is not disposed but the first negative electrode material and the third negative electrode material are disposed.
3. 3. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the framework forming agent comprises a silicate represented by the following general formula (1): [Chemical formula 1] A 2 O·nSiO 2 ... Formula (1) [In the above general formula (1), A represents an alkali metal, and n is 1.6 or more and 3.9 or less.]
4. 4. The negative electrode for a non-aqueous electrolyte secondary battery in accordance with claim 1, wherein the thickness of the second region is 0.5 to 15% of the thickness of the entire negative electrode.
5. 5. The negative electrode for a non-aqueous electrolyte secondary battery according to claim 1, wherein the porous metal body is a foamed metal body.
6. A non-aqueous electrolyte secondary battery comprising the negative electrode for non-aqueous electrolyte secondary batteries according to claim 1 .
Citation Information
Patent Citations
Control method of idle speed
JP1986049147A
Resin composition
JP1988069818A
Nonaqueous electrolyte secondary battery
JP2004259636A
Skeleton forming agent and negative electrode using the same
JP2018085276A
Electrode for secondary battery and method for manufacturing the same
JP2018526791A